A survey of security and privacy in connected vehicles - Othmane, L. B. (Springer New York, 2015)
Electronic control units (ECUs) of a vehicle control the behavior of its devices e.g., break and engine. They communicate through the in-vehicle network. Vehicles communicate with other vehicles and road side units (RSUs) through vehicular ad-hoc networks (VANets), with personal devices through wireless personal area networks (WPANs), and with service center systems through cellular networks. A vehicle that uses an external network, in addition to the in-vehicle network, is called connected vehicle.